2018
DOI: 10.1038/s41419-018-0849-6
|View full text |Cite|
|
Sign up to set email alerts
|

Macrophages confer resistance to PI3K inhibitor GDC-0941 in breast cancer through the activation of NF-κB signaling

Abstract: The PI3K pathway is one of the most dysregulated signaling pathways in epithelial cancers and has become an attractive therapeutic target under active preclinical and clinical development. However, recent clinical trial studies revealed that blockade of PI3K activity in advanced cancer often leads to the development of resistance and relapse of the diseases. Intense efforts have been made to elucidate resistance mechanisms and identify rational drug combinations with PI3K inhibitors in solid tumors. In the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Similar to Flow cytometric analysis, YTE‐17 significantly restrained M2 marker (Arg‐1) and enhanced M1 marker (iNOS) expression, respectively (Figure 3B up). Extensive evidence suggests that the phosphorylation of some known signaling pathways, including ERK, JNK, and STAT3, is markedly enhanced by tumor supernatant stimulation in RAW264.7 cells 34-36 . To further explore the potential mechanism of YTE‐17, we used in vitro models to identify the pathway that could be regulated as YTE‐17 inhibits M2 macrophage polarization.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to Flow cytometric analysis, YTE‐17 significantly restrained M2 marker (Arg‐1) and enhanced M1 marker (iNOS) expression, respectively (Figure 3B up). Extensive evidence suggests that the phosphorylation of some known signaling pathways, including ERK, JNK, and STAT3, is markedly enhanced by tumor supernatant stimulation in RAW264.7 cells 34-36 . To further explore the potential mechanism of YTE‐17, we used in vitro models to identify the pathway that could be regulated as YTE‐17 inhibits M2 macrophage polarization.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have shown that overexpression of AXL in response to therapeutic stress can evolve through a variety of mechanisms, including transcriptional regulation (15,23,24,(49)(50)(51), posttranslational regulation (52,53), and expression of miRNA (54) cytokines, such as TNF-α following anti-PI3K treatment (57), it is tempting to suggest that BYL719 treatment induces the secretion of proinflammatory cytokines, which may downregulate MITF expression and, hence, enhance c-JUN expression.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments performed in vivo proved that pictisilib administration induced the expression of macrophage-associated cytokines and chemokines, macrophage recruitment to the tumor bed, and poor antitumor effect. However, treatment with aspirin and pictisilib decreased macrophage infiltration, tumor growth and pulmonary metastasis (214), highlighting the importance of macrophage-induced NF-κB activation in tumor cells resistant to pictisilib. In line with these findings, TNFα derived from macrophages, turned melanoma cells resistant to MEK inhibition through activation of NF-κB (215).…”
Section: Pi3k Inhibitorsmentioning
confidence: 98%